Extension and Validation of the Self-care Index to Predict Transfer to a Post-acute Care Institution in Internal Medicine Patients / Erweiterung und Validierung des Selbstpflegeindexes bei internistischen Patienten mit dem Ziel eine Verlegung in eine post-akute Nachsorgeinstitution vorauszusagen - Conca Antoinette; Koch Daniel; Regez Katharina; Kutz Alexander; Haubitz Sebastian; Schuetz Philipp; Mueller Beat; Schindler Christian; Spirig Rebecca; Petry Heidi (Sciendo, 2022)
A systematic screening of patients with a need for post-acute care is a helpful support for interprofessional discharge planning teams. We aimed to test self-care abilities, measured by the self-care index (SPI) as predictors of post-acute care transfer and to update the existing SPI prediction model.